Islamizing Contemporary Man: The Approach of Islamic Teachings to Education - Hamidreza Ayatollahy (Universitas Darussalam Gontor, 2025)
The inconsistency of some educational systems in the contemporary world with the educational approaches in Islamic societies has not only led to their inefficacy but also imposed non-divine and even anti-religious values upon Islamic communities. Given the necessity of presenting educational theories aligned with Islamic societies, this article aims to demonstrate the approach Islamic teachings can take towards the foundations of education. These teachings are principally derived from the Quran and the sayings and lifestyles of the Prophet Muhammad and his Household (peace be upon them). Among them, Imam Ja'far al-Sadiq (peace be upon him), the sixth Imam of the Shia, played a prominent role in presenting such intellectual systems based on Quranic insights and the Prophet's conduct. From the collection of Imam Sadiq's practices and sayings, it is possible to extract some features as his intellectual views on education. In this paper, we focus on the educational foundations as derived from his sayings in four domains. We then highlight fourteen value attributes in his educational approach, which can serve as the foundation for structuring the principles of Islamic education and its practical solutions.